A RETROSPECTIVE STUDY ON THE BATHING HABIT OF THE RURAL PATIENTS AROUND BARDHAMAN HAVING RHINOSPORIDIOSIS - Dr. Sudipta Bhattacharyya; Dr. Sohini Ray; Dr. Anway Sen; Dr. Debasish Guha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction Rhinosporidiosis & its etiological agent Rhinosporidium seeberi has been recognised for over a century. Unresolved enigmas in rhinosporidiosis encompass the mode of infection & certain features of histology. The aim of present retrospective study is to study the bathing habit of the immunocompetent rural patients round Bardhaman having Rhinosporidiosis. Material & Methods The current hospital based retrospective research was conducted at Department of Pathology of a tertiary care centre, Bardhaman during the study period of January 2008 to December 2012 among 30 histopathologically diagnosed cases of rhinosporidiosis. Bathing habits & other information of patients was collected & results were analyzed using SPSS version 25.0. Results Most cases were found to fall within the 31-40 years age group (26.7%). 56.3% were male & 46.6% were females. Almost all patients were found to be of low SES (73.3%). Most of the cases used pond water 21 (70%) for bathing followed by rivers 4 (13.3%), deep tubewell 3 (10%) & piped water 2 (6.7%). The most common symptoms found in patients were nasal block 4 (13.3%), nasal mass 15 (50%), eyelid mass 2 (6.7%). The involvement site were sino-nasal area 20 (66.7%), nasopharyngeal 6 (20%), ocular area 3 (10%) & aural area 1 (3.3%). Conclusion The socioeconomic level, outdoor bathing, & cultural practices in rural areas are the primary factors contributing to new cases. A prompt governmental initiative to cleanse public water bodies & enhance public health education via healthcare professionals & non-governmental organisations is essential to reduce the occurrence of rhinosporidiosis.